The Impact of Corporate Governance on Banks Profitability in Nigeria - Foluso Ololade Oluwole (Financial Markets, Institutions and Risks)
The major concern of regulatory authority overtime is on the need to enhance sound practices among banks through the improvement of corporate governance; therefore this research examined the effect of corporate governance on commercial banks profitability in Nigeria. The study covered the period of 2009 to 2018 and secondary data were obtained from the audited financial statement of the selected banks which are Guarantee Trust Bank Nigeria PLC, Zenith Bank PLC and First Bank of Nigeria PLC. Fixed effect regression technique was used to examine the effect of Audit Committee Size (ACS), Board Size (BS), Audit Committee Number of Meeting (ACNM) and Board Number of Meeting (BNM) on earnings per share (EPS) of the selected banks. The independent variables results showed a positive and significant relationship on Earnings per share of the banks with coefficient and probability(prob.) value of the variables as follows: audit committee size(0.6241;0.0109), board size(0.4349;0.007) and board number of meeting(0.0356) had positive and significant effect on earnings per share of the banks respectively. However, negative and significant relationship was established between audit committee number of meeting and earnings per share with a coefficient and probability value of -1.0781 and 0.0001 respectively. With the F-Stat. of 2.84 and a prob. of 0.025, all the null hypotheses were rejected and the alternative hypotheses accepted, indicating that all the independent variables significantly affect the dependent variable. The study concluded that corporate governance enhances commercial banks performance in Nigeria. It therefore recommended that attention should be paid to the audit committee size, board size and board number of meetings since an increase in them leads to increase in the earnings per share while the audit committee number of meetings should be reduced as it affects the earnings per share negatively. The regulatory authority should formulate strong policy frameworks that would ensure that commercial banks constantly comply with corporate governance standard set by the authority.